Liability protection, director compensation, and incentives - Aguir, Iness; Burns, Natasha; Mansi, Sattar A.; Wald, John K. (Journal of Financial Intermediation, 2014)
We examine the effect of liability protection on the compensation of directors and on takeover outcomes. Consistent with the hypothesis that directors require additional compensation if they bear liability, we find that director compensation is higher for firms that provide less liability protection. Examining takeovers, we find evidence that takeovers of firms with protected directors are less likely to succeed. Moreover, firms with protected directors are more likely to accept a lower bid premium, and this finding is consistent with protected directors having reduced incentives to negotiate for the highest possible price during the acquisition. Overall, the results are consistent with the notion that director liability provisions have a significant impact both on director compensation and director duty.